69. IMPROVED IVF SUCCESS OF COMBINED PGT-M AND PGT-A APPLICATIONS. (August 2019) - Unsal, E.; Aktuna, S.; Aydin, M.; Ozer, L.; Baltacı, V.
Abstract : Introduction: Preimplantation Genetic Testing (PGT) has been performed since 1989 and utilized in the diagnosis of all genetic conditions at preimplantation stage (1 ). In the previous years, only a disorder could be diagnosed with the use of multiplex nested PCR in PGT applications. Increased use of trophectoderm biopsy and vitrification together with Whole Genome Amplification (WGA) technology enabled the detection of single gene disorders together with 24 chromosome screening. This approach allowed us to select healthy and chromosomally euploid embryos. Even though single gene disorder carrier patients are mostly young and fertile, they still have high risk of spontaneous miscarriage. In the recent years, it has been reported that when the embryos are screened for aneuploidy (PGT-A) in addition to single gene disorder testing (PGT-M), pregnancy rates can be increased from 45% to 68% and spontaneous miscarriage rates decreased from 15% to 5%. 34 single gene disorder patients, whose embryos were found to be healthy in terms of single gene disorder, were included in this study and these embryos were further screened for aneuploidy using Next Generation Sequencing (NGS) technology (2 ). Materials & Method: On the 5th and 6th days of embryonic development, WGA was performed using SurePlex DNA Amplification System (Illumina, USA) and DOPlify (PerkinElmer Health Sciences - Australia). Following multiplex nested PCR on WGA samples, fragment analysis for haplotyping and sequence analysis for mutation detection were performed. Embryos found to be suitable for transfer regarding the single gene disorder have further been screened for aneuploidy using NGS technology with VeriSeq PGS Kit (Illumina, USA). Results: This study was conducted for single gene disoder and 24 chromosome screening in 44 patients with an average age of 34. 280 embryos derived from these patients were included in PGT-M. Among 153 embryos that were found to be suitable for transfer after PGT-M, PGT-A was performed on 121 embryos upon patients' requests and 49% of these embryos were euploid. Embryo transfer could not be performed in 12 patients due to the absence of euploid embryos. According to the data we acquired, 64% pregnancy was achieved in the rest of the patients. Conclusion: While pregnancy ratio can be improved with this approach, Allele drop out (ADO) and contamination errors are still major limitation which can lead to misdiagnosis of embryos. ADO ratio was demonstrated to be 25% in PGT for blastomere cells, whereas this ratio drops down to 5% when 5-7 cells obtained by trophectoderm biopsy are tested. Thus trophectoderm cells are more appropriate for PGT-M applications combined with PGT-A. Since stable and homogenous amplification of the entire genome is a crucial step, optimised WGA technologies will be a key factor in these applications.